Tinkering with the Machinery of Death: An Analysis of Juror Decision-Making in Texas Death Penalty Trials During Two Statutory Eras. (2nd January 2017) - Vartkessian, Elizabeth S.; Sorensen, Jon R.; Kelly, Christopher E.
Abstract : The Texas death penalty statute originally approved by the United States Supreme Court in Jurek v. Texas (1976) was legislatively amended as a result of the Court's decision in Penry v. Lynaugh (1989). The changes were intended to focus on increasing jurors' ability to give mitigating effect to evidence in sentencing. Using data from the Capital Jury Project, we compared juror comprehension of sentencing guidelines, punishment responsibility, and deliberations in sentencing among a sample of 123 Texas jurors who deliberated under the Jurek and Penry statutes. In each area, we found that the amended statute failed to guide capital juror decision-making as intended.